THE IMPACT OF FLEXIBLE WORK POLICIES AND WORK-LIFE BALANCE ON EMPLOYEE PERFORMANCE (GRAB DRIVER CBD POLONIA) - Muhammad Zakiul Fuad Batubara; Nursakinah Ritonga; Lisa Iryani; Nursanjaya; Sufi (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The development of the modern workplace demands that companies create adaptive work systems, including through the implementation of flexible work policies and efforts to maintain a balance between work and personal life for employees. This study aims to determine the effect of flexible work policies and work-life balance on employee performance, specifically for Grab drivers in the Polonia CBD area. This study used a quantitative approach with data collection techniques through distributing questionnaires to respondents selected non-probabilistically. The data obtained were analyzed using multiple linear regression methods with the assistance of statistical software. The results showed that flexible work policies did not have a significant impact on individual employee performance. Conversely, work-life balance was proven to have a positive and significant impact on improving employee performance. Meanwhile, together, both variables made a significant contribution to employee performance. From these findings, it can be concluded that efforts to create a balance between work and personal life have a more significant impact on performance than simply providing flexibility in work. Therefore, companies are advised to integrate flexible work policies with employee welfare support programs to create a more productive and sustainable work environment.